A reduced Ginzburg–Landau model in ℝn. Issue 16 (10th December 2021) - Fan, Jishan; Jing, Lulu; Nakamura, Gen; Tang, Tong
ABSTRACT: In this work, we consider a reduced Ginzburg–Landau model in which the magnetic field is neglected. First, we show the well-posedness of weak solutions and strong solutions in a bounded domain Ω ⊂ R n . Finally, we prove the well-posedness of smooth solutions when Ω := R n ( n ≥ 3 ) .